The Effect of Yellow Pumpkin Pudding (Cucurbita Moschata) on Sleep Quality in Postpartum Mothers in the Working Area of the Dinoyo Health Center, Malang - Novida Ariani; Ningrum Paramita Sari; Putri Hainun Sasabela (Formosa Journal of Sustainable Research, 2023)
Sleep is a biological process experienced by humans, as well as the most basic human needs. Proper rest and sleep are just as important for health as nutrition and adequate exercise. Sleep disorders can be overcome with non-pharmacological measures to prevent the risk of anxiety that occurs in postpartum mothers. Pumpkin containing L-tryptophan, zinc, and magnesium. to determine the effect of pumpkin pudding (Curcubita moschata) on sleep quality for postpartum women in the Working Area of Puskesmas Dinoyo, Malang. Methods: The research design is quasi experiment using non-equivalent control group design. Analysis by Paired t-test. This study used a sample of 32 postpartum mothers who matched the inclusion and exclusion criteria in the Working Area of Puskesmas Dinoyo, Malang. The participant received pumpkin pudding or milk pudding every day for a week. : showed that there was an effect of pumpkin pudding (Curcubita moschata) on sleep quality for postpartum mothers shown that p value = 0.000  (p-value <0.05). There is an effect of pumpkin pudding (Curcubita moschata) on sleep quality for postpartum women in the Working Area of Puskesmas Dinoyo, Malang